Does History Matter? The Old and the New World of Microfinance in Europe and Asia - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2005)
In a number of European countries microfinance evolved from informal beginnings during the eighteenth and nineteenth centuries as a type of banking of the poor, juxtaposed to the commercial and private banking sector. Almost from the onset, microfinance meant financial intermediation between microsavings and microcredit, and was powered by intermediation. Legal recognition, regulation and mandatory supervision evolved in due course and led to a process of mainstreaming during the twentieth century when microfinance became part of the formal banking sector. In Germany, the former microfinance institutions now account for around 50% of banking assets; outreach is to around 90% of the population. Microfinance in Asia presumably has a much longer history, though little seems to be known about the early history of the hui in China, the chit funds in India, the arisan in Indonesia or the paluwagan in the Philippines, to name but a few. Financial institutions of indigenous origin, most of them informal, are still exceedingly widespread but have been largely ignored in financial sector development. There are exceptions on a limited scale, as in India where chit funds are regulated and in Indonesia with its highly diversified rural and microfinance sector where various forms of informal financial institutions have been registered and eventually regulated throughout the twentieth century. Not a single country has made indigenous forms of microfinance a pillar of its modern financial system. As neither commercial nor development banks nor state-dominated but unsupervised cooperatives delivered to the rural and urban masses, credit NGOs, during the 1970s, ushered in what came to be known as the microcredit revolution. Powered by donor support and international publicity, Grameen Banking became the new model of microcredit, its founder the prophet of the microcredit movement. The term microfinance, originally meant to comprise financial intermediation between savers and borrowers, was created only in 1990. In the mid-1990s it was taken up by CGAP, the donor Consultancy Group to Assist the Poor, which has turned the microcredit revolution into the microfinance revolution and professionalized microfinance. To some extent it has reinvented history not only in Europe but also in Asia and elsewhere where micro- or informal finance and indigenous banking have always been based on principles of self-reliance, viability and sustainability. CGAP re-discovered the principles, but not the indigenous financial sector, be it informal or formal. Has the time come to revisit indigenous finance in Asia and re-examine its potential for upgrading, mainstreaming and innovating (Seibel 1997, 2001)? India may serve as an example: far older and more complex, yet also far less conclusive, than the European experience.
Keywords: 330